An Empirical Assessment of the Impact of Blockchain Technologies on the Effectiveness of the Supply Chain Development - Marat Rashitovich Safiullin; Leonid Alekseevich Elshin; Alia Aidarovna Abdukaeva (International Journal of Supply Chain Management, 2020)
Abstract—The purpose of this paper is to review the existing literature on blockchain technology, present some trends and consider its potential value in supply chain management (SCM) of market. In modern economic conditions, the financial market integrated into the global economy is of fundamental importance for the development of the national economic system. In order to maintain and develop economy, the financial sector is constantly looking for ways to optimize its business processes and operations. Today, blockchain technology is considered by many participants in the financial market as a tool that forms the innovative potential of the industry providing a number of additional effects. It should be noted that despite the very high interest on the part of international and national financial institutions, enterprises of the real sector of the economy in the distributed data storage technology, studies on the problems of assessing the use of the potential of blockchain platforms in the socioeconomic environment, their theoretical understanding is not often demonstrated. Existing works, as a rule, reveal either the technical side of the object under study, or the regulatory or legal aspects of the applicability of blockchain technologies in the national economy. In this regard, this work attempts to overcome this conditional vacuum of understanding in order to make up for conditions with questions revealing other aspects of the subject of research, for example, such as the economic and social effects of introducing blockchain technologies into the activities of business entities. A formalized assessment of the development prospects of the banking sector in the new institutional economic environment is carried out on the basis of the assessment of the emerging effects caused by the integration of distributed data storage technologies into the system of operational processes in credit institutions